2015
DOI: 10.1016/j.bjorl.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Hearing preservation and cochlear implants according to inner ear approach: multicentric evaluation

Abstract: The hearing preservation occurred in 89.4% of cases. There was no significant difference between the forms of inner ear approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…The proportion of round window approach and cochleostomy approach was different between the two groups, which was statistically insignificant (p = 0.083; Fisher's exact test). In addition, it was reported that the rate of HP was not different between the two approaches [Guimaraes et al, 2015;Sun et al, 2015]. The electrode array type was also different between the two groups.…”
Section: Discussionmentioning
confidence: 91%
“…The proportion of round window approach and cochleostomy approach was different between the two groups, which was statistically insignificant (p = 0.083; Fisher's exact test). In addition, it was reported that the rate of HP was not different between the two approaches [Guimaraes et al, 2015;Sun et al, 2015]. The electrode array type was also different between the two groups.…”
Section: Discussionmentioning
confidence: 91%
“…The same paper mentions further "a small number of studies reporting on children fitted with EAS have recently been published by Skarzynski et al" In its summary it says "Skarzynski and his group have demonstrated convincing results in their first studies on children" and further "however, Skarzynski stressed that this kind of surgery on children should not be attempted without significant successful experience with adults" and still further "by introducing this method, it became possible to improve hearing preservation, with rates going up to 95-100% in most EAS candidates." Guimares et al in the Brazilian Journal of Otorhinolaryngology in 2015 have said: "Some classifications for hearing preservation have been proposed to assess the degree of preservation of residual hearing, and the most commonly employed is that proposed by Skarzynski (…)" [29].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, exposure of the dura is required and complications such as epidural hematoma, subdural hematoma, temporal lobe infarction and dural tears with cerebrospinal fluid leak can arise, although rare [4]- [6].…”
Section: Discussionmentioning
confidence: 99%